Producing Kombucha Beads by Spherification: Effect of Alginate Concentration and Exposure-Time on Release Behaviour of Polyphenolic Compounds - Dewi Cakrawati; Dwi Lestari Rahayu; Yatti Sugiarti; Mustika Nuramalia Handayani (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Encapsulated kombucha was an alternative kombucha product to be added to food product conveniently. This study was investigated the effect of sodium alginate concentration and exposure time on the release of bioactive compounds namely total phenolic content, antioxidant capacity also reducing sugar. Stability of kombucha beads in simulated gastric juice was also investigated based on viable bacteria. The result shows that concentration of 1-4% sodium alginate produce tear-shape like beads. The size of kombucha beads increase as the increasing of sodium alginate concentration. Low pH value of initial kombucha lead to strong gel formed during gelation that resulted in low release of polyphenolic compounds as well as antioxidant capacity from kombucha beads. The total phenolic content released from kombucha beads was 0.098 ± 0.01 mg GAE/100 g beads. Microbial load after simulated gastric juice was in the range of 178-1398 cfu/g bead. This study highlighted potential of alginate beads for encapsulating polyphenolic compounds as an innovative for food application. Further study needed to understand physical properties of kombucha beads at different concentration of sodium alginate.